Translating Art Catalogues: Theoretical and Practical Issues - Pireddu, Silvia (Imaginations, 2020)
This article addresses the translation of exhibition catalogues in the context of cross-medial communication by discussing a small corpus of multilingual texts. Multilingual art catalogues are a standardized genre, which collect academic, explanatory, and descriptive writings. These hybrid volumes pose problems related to semantic and communicative translation, terminology, specialized language, and emotive discourse by involving the visual. In a world where art is communicated with diverse media, publishers should reconsider the format of exhibition catalogues, as translation across media and languages can play a crucial role in marketing art and culture.